Asian American and Pacific Islander substance use treatment admission trends. (1st February 2017) - Sahker, Ethan; Yeung, Chi W.; Garrison, Yunkyoung L.; Park, Soeun; Arndt, Stephan
Highlights: Asian Americans/Pacific Islanders are increasing in substance abuse treatment admissions. Nebraska, North Dakota, South Dakota, Texas, and Florida increased the greatest. Problem Rx opioids, the oldest, and youngest clients showed large increasing trends. Abstract: Background: A national analysis of Asian Americans and Pacific Islanders (AAPI) substance use treatment admissions has yet to be studied. We sought to explore admission trends for AAPI, demographic and treatment variable change, and individual state admission change over time. Methods: We used retrospective time-series logistic regression treating year as a predictor of yearly treatment admission trends, between-state test for heterogeneity of treatment effects among states' AAPI admissions, and percent-changes of AAPI demographic and treatment characteristics. Participants included AAPI (n = 135, 356) and comparison non-AAPI (n = 8, 938, 982) treatment groups' first-time admissions (N = 9, 074, 338) in United States treatment centers receiving public funding from 2000 to 2012. Results: AAPI demonstrated a greater increase in admissions than non-AAPI from 2000 to 2012 ( p < 0.0001; OR = 1.02, 95% CI = 1.019–1.022). Large percent increases were demonstrated in multiple demographic and treatment characteristic, most notably in prescription opioids as a problem substance, age of first use for the oldest and youngest groups, and homelessness. In addition, trends are provided for individual states to help prioritize resource need. Conclusions: The present demographic and treatment characteristics revealed specific variables that may help to improve a culturally competent understanding of increasing risk factors among AAPI clients. The present findings may help to demonstrate which states may need to increase AAPI-specific resources and interventions.